1995
DOI: 10.1164/ajrccm.151.2.7842216
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary lymphangioleiomyomatosis: a report of 46 patients including a clinicopathologic study of prognostic factors.

Abstract: The clinical and pathologic features of 46 patients from Japan, Korea, and Taiwan with pulmonary lymphangioleiomyomatosis (LAM) were studied. Only two (5%) among 40 evaluable treatments were assessed to be effective. Some prognostic factors of LAM were recognized. A reduction of the forced expiratory volume in one second/forced vital capacity (FEV1/FVC) ratio was a poor prognostic factor at 2 yr after the first examination, with a statistically significant difference (p < 0.05). An increase in the percentage o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
235
2
28

Year Published

1998
1998
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 329 publications
(275 citation statements)
references
References 18 publications
5
235
2
28
Order By: Relevance
“…It has been shown that the smooth muscle found in PLAMis similar histologically and immunohistochemically to that found in angiomyolipoma (1 1). The suggestion that PLAMis aformefruste of tuberous sclerosis is strengthened by the findings that patients with LAM also have angiomyolipoma (15). But in the present case, renal angiomyolipoma wasnot seen on CTscans.…”
Section: Discussioncontrasting
confidence: 41%
“…It has been shown that the smooth muscle found in PLAMis similar histologically and immunohistochemically to that found in angiomyolipoma (1 1). The suggestion that PLAMis aformefruste of tuberous sclerosis is strengthened by the findings that patients with LAM also have angiomyolipoma (15). But in the present case, renal angiomyolipoma wasnot seen on CTscans.…”
Section: Discussioncontrasting
confidence: 41%
“…The yearly rate of change in percent predicted FEV 1 and Dlco was estimated as previously reported. 15 Univariate and multivariate regression analyses were performed to identify factors related to the pulmonary function rate of decline.…”
Section: Discussionmentioning
confidence: 99%
“…Chest CT scans may be useful for providing evidence of bullous formation (9). Characteristics of CT findings in patients with LAMinclude multiple well-defined cystic air spaces surrounded by uniformly thin walls, distributed diffusely throughout both lungs (5,10). The differential diagnosis for LAMincludes emphysema and Langerhans cell granulomatosis.…”
Section: Case Reportmentioning
confidence: 99%
“…The iso-density masses in the retroperitoneum detected by abdominal CT and the abdominal mass extracted previously might have been LAM. Kitaichi et al (10) reported the clinical and pathologic features of 46 patients with pulmonary LAMfrom Japan (39 patients), Korea (5 patients) and Taiwan (2 patients). They described that the patients were all females, meanage at onset was 32.0+8.9 year (range 20 to 63 year), and major symptoms at the time of onset were dyspnea (57%) and cough (33%).…”
Section: Case Reportmentioning
confidence: 99%